Analysis of the Basic Science Questions on the Orthopaedic In-Training Examination From 2014 to 2019. Issue 23 (1st December 2021) - Shen, Tony S.; Driscoll, Daniel A.; Ellsworth, Bridget K.; Premkumar, Ajay; Lebrun, Drake G.; Bostrom, Mathias P. G.; Cross, Michael B.
Abstract : Introduction: The Orthopaedic In-Training Examination (OITE), produced by the American Academy of Orthopaedic Surgeons (AAOS), plays an important role in the educational mission of orthopaedic residency programs nationwide. An up-to-date understanding of this examination is critical for programs to develop an appropriate curriculum and for individuals to identify learning resources. This study presents an updated analysis of the basic science section of the OITE from 2014 to 2019. Methods: All questions from the OITE from 2014 to 2019 were reviewed. Each question from the basic science section was categorized by topic and taxonomy. The use of radiographic images or other clinical media was recorded. The reference section was analyzed for bibliometric factors. Pearson chi-square tests were used as appropriate for statistical comparison. Results: In total, 185 of 1, 600 questions in the basic science section were used over the 6-year study period (11.6%). The proportion of basic science questions ranged from 10.7% to 12.0% from year to year. The most frequently tested topics were cellular and molecular biology (23.8%), physiology/pathophysiology (16.8%), and pharmacology (10.8%). There was an increase in the number of biostatistics questions from 2017 to 2019 compared with the number from 2014 to 2016 ( P = 0.02). The most common taxonomic category was knowledge recall (89.7%). A total of 383 references were cited from 122 sources. The 3 most common sources accounting for 44.4% of all citations were produced by the AAOS. Discussion: The basic science section of the OITE accounts for approximately 11% of all questions, with the most common taxonomy being knowledge recall (89.7%). Recent tests have emphasized biostatistics, highlighting the importance of incorporating biostatistics into residency education. Reference materials produced by the AAOS were highly cited in this section.